THE HIGH-PERFORMANCE PLAYBOOK: STRATEGIES FOR MOTIVATING AND RETAINING TOP TALENT - Synthia; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2026)
This article addresses the critical business challenge of employee retention in the competitive modern talent market. The objective is to provide a systematic, actionable framework for organizations to motivate and retain their highest performers. The methodology synthesizes contemporary management research, organizational psychology principles, and best practices from industry case studies into a cohesive